On the Relation between Strength and Stiffness of Cable Tray. (8th April 2021) - Ma, Yongqi; Ding, Weidong; Ding, Chao; Ma, Hang
Abstract : In order to realize the optimal design of the cable supporting system for the purpose of material saving and energy saving and green manufacturing, the strength-stiffness ratio is proposed in the paper in nondimensional form, which defines quantitatively the relation between the static load strength and stiffness of the cable tray. On the premise of ensuring service safety, the correlation between the strength and stiffness of the cable tray under static load is discussed extensively through the theoretical analysis of the mechanical model. The weakest link in the carrying capacity of the cable tray as well as the issue that needs to pay attention is proposed in the process of design and the test of the cable tray. A reasonable strength-stiffness ratio will help to make full use of the potential of material strengths. The value of the strength-stiffness ratio is obtainable by means of the finite element method or by the loading test of the cable tray. It is shown through the analysis that the value of the strength-stiffness ratio being setting in the range close to but less than 1 will make comparatively reasonable material utilization and will help the deflection test going smoothly to obtain a relatively safer allowable working load for the cable tray.